2017
DOI: 10.21767/1791-809x.1000533
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Obstetric Danger Signs during Pregnancy in Debre Berhan, Ethiopia

Abstract: Background: Pregnancy danger signs are the major health problems and cause of mortality among women in developing countries. Majority (99%) of maternal death occurred in developing countries from the total of 529,000 mothers' death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 5 publications
6
21
1
Order By: Relevance
“…In our study, women recognized more danger signs that might occur during pregnancy, followed by the intrapartum and postpartum periods. Our finding is in agreement with a study conducted in Ethiopia, where the participants were most knowledgeable about danger signs during their pregnancy period [20]. In contrast to our findings, a study conducted in Uganda found that the participants' knowledge of at least one danger sign was highest during childbirth and the postpartum period [8].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, women recognized more danger signs that might occur during pregnancy, followed by the intrapartum and postpartum periods. Our finding is in agreement with a study conducted in Ethiopia, where the participants were most knowledgeable about danger signs during their pregnancy period [20]. In contrast to our findings, a study conducted in Uganda found that the participants' knowledge of at least one danger sign was highest during childbirth and the postpartum period [8].…”
Section: Discussionsupporting
confidence: 91%
“…The difference may be due to study period difference and increasing the number of staffs which providing counseling on danger signs during antenatal, childbirth and postnatal period. The finding of this study was comparable with the same study conducted in Debre berhan city administration 61.1% [18]. Vaginal bleeding during childbirth was also mentioned by about 60% of the respondents, while persistent headache and blurred vision was mentioned by 24.9%, which was higher than study conducted in aleta wendo district, sidama zone 55 and 7%.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is in agreement with (Abrahim et al, 2017) inEgypt, (Gebrehiwot et al, 2014) (5,6,7) Also, this finding was concur with a study conducted by (Solomon et al, 2014) in Central Ethiopia, (Mwilike et al, 2013) in Tanzania , (Okura et al, 2012) in Jordan , (Rashad et al, 2010) in Egypt, who reported low levels of knowledge about danger signs and symptoms . (8,9,3,10) Regarding association between pregnant women's knowledge women's and study variables this study shows that there are a statistical significant differences between pregnant women's knowledge and socio demographic variables, while no statistical significance differences between pregnant women's knowledge and reproductive characteristics, this finding agree with that reported in Jordan by (Okura et al, 2012), in Egypt by (Rashad, 2010), in Egypt conducted by (Abrahim et al, 2017), in North Ethiopia by (Nurgi, et. al., 2014), in Debra Town, Ethiopia by (Solomon et al, 2014), ,in Ethiopia by (Ndudi et al ,2015) , in Debar Towne in Ethiopia by (Mengesha et al , 2012 ) and in Tanzania by (Mwilke et al, 2007).…”
Section: Discussionsupporting
confidence: 87%